La perdida de la patria potestad por abandono injustificado y su relación con el principio de corresponsabilidad paternal - Ferre Capuñay, Pablo Jenner (2018)
In the present research work is developed in accordance with the budgets established by the titling system of the Technical University of Machala prior to Obtaining the Degree of Lawyer of the Courts and Tribunals of the Republic of Ecuador, whose research topic is LA LOSS OF THE PATRIA POTESTAD FOR UNJUSTIFIED ABANDONMENT AND ITS RELATIONSHIP WITH THE PATERNAL PRINCIPLE OF CORRESPONSIBILITY, whose development allowed to elucidate and study the legal budgets related to the definitive loss of the exercise of parental authority, by the persons that are legally designated for this task when allegedly abandoned the child or have failed to fulfill their duty of care in application of the principle of parental responsibility